Clinical spectrum and risk factors for complicated disease course in children admitted with SARS-CoV-2 infection. (2020)
In Spain, the first case of coronavirus disease 2019 (COVID-19), caused by the novel coronavirus known as SARS-CoV-2, 1 was detected on January 31, 2020. In the weeks that followed, SARS-CoV-2 spread through the entire country, and the Community of Madrid was the region hit the hardest